“A highly favoured people”:: The Planter Narrative and the 1928 Grand Historic Pageant of Kentville, Nova Scotia - Norman, Alison (Acadiensis)

(untitled) (The Department of History at the University of New Brunswick, 2009)
The 1928 historic pageant in Kentville, Nova Scotia, offers a fascinating example of the crucial role that a community’s narrative self-conception plays in the construction of its history. As a tale of the Planter’s presence in the Annapolis Valley, the pageant was both celebratory and exclusionary. The community elite created a story about the providential arrival of the Planters beginning in 1760 that served to minimize the Planter impact on both the Acadians and Mi’kmaq while emphasizing the progress of the Planter descendants in the modern town. Directed by a woman, the pageant was also a gendered narrative in which the expanding role of women in public life was highlighted.